AvGI, an index of genes transcribed in the salivary glands of the ixodid tick Amblyomma variegatum - Nene, Vishvanath M.; Lee, D.; Quackenbush, J.; Skilton, Robert A.; Mwaura, S.; Gardner, M.J.; Bishop, Richard P. (Elsevier, 2002)
Random clones from a cDNA library made from mRNA purified from dissected salivary glands of feeding female Amblyomma variegatum ticks were subjected to single pass sequence analysis. A total of 3,992 sequences with an average read length of 580 nucleotides have been used to construct a gene index called AvGI that consists of 2,109 non-redundant sequences. A provisional gene identity has been assigned to 39% of the database entries by sequence similarity searches against a non-redundant amino acid database and a protein database that has been assigned gene ontology terms. Homologs of genes encoding basic cellular functions including previously characterised enzyme activities, such as stearoyl CoA saturase and protein phosphatase, of ixodid tick salivary glands were found. Several families of abundant cDNA sequences that may code for protein components of tick cement and A. variegatum proteins which may contribute to anti-haemostatic and anti-inflammatory responses, and, one with potential immunosuppressive activity, were also identified. Interference with the function of such proteins might disrupt the life cycle of A. variegatum and help to control this ectoparasite or to reduce its ability to transmit disease causing organisms. AvGI represents an electronic knowledge base, which can be used to launch investigations of the biology of the salivary glands of this tick species. The database may be accessed via the World Wide Web at http://www.tigr.org/tdb/tgi.shtml.